Public Policy in Brussels Regulation I: Yesterday, Today and Tomorrow - Tomaž Keresteš (LeXonomica, 2017)
This article deals with the notion of public policy in the framework of Brussels system the past, present and future. Author concludes that Brussels I Recast Regulation did not change much regarding the public policy issue. Even though initially there were thoughts that it should be removed from the system altogether, at the end only the exequatur has been abolished, but the public policy exception remained. As there was no significant change related to the public policy exception in the last Regulation, all the case law made under Brussels Convention and Brussels I Regulation is still applicable. This means that the public policy exception can be based on either procedural or substantive public policy arising out of national legal order and suitable for international relations (international public policy). There are also emerging contours of pure EU public policy. However, this one is still not supplementing the public policy based on national legal rules as this is a hallmark of European diversity.